Penerapan Sistem Informasi Geografis Pemetaan Apotek di Baturaja Berbasis Web - Agustin, Ade Vanecsya; Monyca, Delta; Herlena, Ayu; Pujianto, Pujianto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the application of web-based Geographic Information Systems (GIS) in mapping the locations of pharmacies in Baturaja and their role in facilitating public access to health service information. The research method used is descriptive with a system development approach, supported by literature studies, field observations, and pharmacy data analysis. Location data was collected by recording addresses and geographical coordinates, then processed and presented in a web-based GIS application. The results showed that the developed system was able to display the distribution of pharmacies clearly and informatively, provide detailed information on pharmacies, and support data management through create, read, update, and delete (CRUD) features. The existence of this system makes it easier for the community to find the nearest pharmacy location more quickly and accurately. However, GIS implementation still faces obstacles in the form of the need for accurate coordinate data and dependence on stable internet access. Overall, web-based GIS has significant potential as a means of supporting the provision of effective health service information in the Baturaja area.